A new species of the genus Atractus from the Northwestern Argentina (Serpentes, Colubridae) - Scrocchi, Gustavo (1991)
A new species of Atractus from the western subtropical region of the Jujuy and Salta provinces (Argentina) is described. The similarities of its morphological features with the species of the Atractus elaps group from eastern alto-Amazonian slopes of Peru and Ecuador are reported.